Estudo das mutações IVS10NT-11G>A, V388M, R261Q, R261X, R252W E R408W no gene da fenilalanina hidroxilase em pacientes com fenilcetonúria do estado de Mato Grosso - Costa, Roseli Divino (2017)
Phenylketonuria (PKU) is an autosomal recessive inborn error of metabolism. The classic form is caused by the deficiency in the enzyme phenylalanine hydroxylase (PAH) which catalyzes the hydroxylation of phenylalanine to tyrosine. Phenylketonuria (PKU) is detected and treated in Brazil at the National Newborn Screening Reference Services present in all Brazilian states. We tested for the IVS10nt-11G>A, V388M, R261Q, R261X, R252W and R408W mutations of the PAH gene in a sample of 19 patients being treated for PKU at the Newborn Screening Reference Service for the State of Mato Grosso. This study is crosssectional and descriptive and the 19 PKU patients in the study were detected over a 12 year period of newborn screening (2003 – 2015). Polymerase chain reaction (PCR) and specific restriction enzymes digestion were the techniques applied for the molecular analysis. Among the 19 patients that participated in this study 4 (21.1%) had two alleles identified; 5 (26.21%) patients had only one allele identified, and 10 (52.6%) were not found to have anyone of these six mutations. It was possible to identify 13/38 alleles, corresponding to 34.21% of the PAH alleles in the sample. The most prevalent mutation was V388M (13.2% of the alleles) followed by R261Q (10.1%) and IVS10nt-G>A (7.9%). Mutations R261X, R252W and R408W were not found. The most frequent types of mutations were missense, in 8 patients (18.4%) and splice in 4 patients (10.52%). Applying the model proposed by Guldberg et al. (1998), a genotype/phenotype correlation was obtained for the 4 patients with two identified mutations, all of whom had classic phenylketonuria. The predicted phenotype was moderate/mild or moderate PKU for 3 of these 4 classical PKU patients and the prediction coincided with the diagnosis of classic PKU in only 1 patient. The incidence of PKU for the State of Mato Grosso for the period from 2003 to 2015 was estimated to be 1:33,342 live births. The average coverage of the Newborn Screening Reference Service program for the State of Mato Grosso for this same period was 75.2% of all newborns. The mutations identified in this study were also found in several Brazilian studies, however, at a lower frequency than previously published data.